2017
DOI: 10.1186/s12917-017-1293-z
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling in pbMEC – in search of molecular biomarkers to predict immunoglobulin production in bovine milk

Abstract: BackgroundOptimization of the immunoglobulin (Ig) yield in bovine milk used as therapeutic immune milk or whey for the prevention of Clostridium difficile-associated diarrhea in humans is of great importance to improve the economic efficiency of production. Individual dairy cows have diverse immune responses upon vaccination, resulting in a variable Ig yield in blood and milk. Therefore, it is advisable to pre-select cows with the best ability to produce and secrete high yields of specific Igs.ResultsThe gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Finally, the markers ARS-BFGL-NGS-107651 and BTB-00141133 (located at ~84.8 Mb on BTA3) and BTA-64483-no-rs (located at 43.14 Mb in BTA28) mapped close to a QTL for SCS according to the Cattle QTL database. When searching for the nearest genes, we found that ARS-BFGL-NGS-107651 and BTB-00141133 (which were in high LD, r 2 = 0.92) corresponded to intron variants of the nuclear factor IA (NFIA) and BTA-64483no-rs mapped at 25 Kb from mitogen-activated protein kinase 8 (MAPK8), genes that play a role in immune system (Fazi et al, 2005;Hillreiner et al, 2017).…”
Section: Gwas Gene-set Enrichment and Pathway-based Analysesmentioning
confidence: 99%
“…Finally, the markers ARS-BFGL-NGS-107651 and BTB-00141133 (located at ~84.8 Mb on BTA3) and BTA-64483-no-rs (located at 43.14 Mb in BTA28) mapped close to a QTL for SCS according to the Cattle QTL database. When searching for the nearest genes, we found that ARS-BFGL-NGS-107651 and BTB-00141133 (which were in high LD, r 2 = 0.92) corresponded to intron variants of the nuclear factor IA (NFIA) and BTA-64483no-rs mapped at 25 Kb from mitogen-activated protein kinase 8 (MAPK8), genes that play a role in immune system (Fazi et al, 2005;Hillreiner et al, 2017).…”
Section: Gwas Gene-set Enrichment and Pathway-based Analysesmentioning
confidence: 99%